KETERSEDIAAN OBAT ANTI NYERI DI APOTEK KECAMATAN WONOASRI KABUPATEN MADIUN - Endah Astuti Astuti; Risma Sakti Pambudi Astuti; Rita Septiana Astuti (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
Pain is a disease experienced by all people. Analgesics are a class of drugs mostoften used for the treatment of pain. Good planning was needed as a basis for drugmanagement activities to determine drug needs to ensure the availability ofpainkillers. This study aims to provide an availability of analgesic drugs in 3(three) pharmacies in Wonoasri District, Madiun Regency.This research was adescriptive study using a retrospective survey method, which was directed atpresenting information about the availability and use of painkillers through theresearch process. The data were obtained from the Pharmacy in Wonoasri District,Madiun Regency. This research material was in the form of data on drugavailability and data on the use of painkillers for the period July to December2019. The data obtained were then processed using the formula for the number ofdrugs available divided by the number of monthly average usage. The level ofdrug availability was seen in months.Based on the results of the study, it wasfound that the value of the availability of painkillers at the Pharmacy of WonoasriDistrict, Madiun Regency for the period July-December 2019 was the Diclofenacdrug with an availability value of 7.8 months, 9.1 and 13.1 months. While thelowest is Mefenamic Acid Drug. Medicines provided for health services at thepharmacy must match the drug needs and must be at least the same as the stockduring the waiting time for drug arrival